Vegetation and Climate - Breckle, Siegmar-W.; Rafiqpoor, M. Daud. (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2022)
Vegetation, soil and climate are the most important components of ecological systems. The book presents a compact synthesis of our current knowledge of the ecology of the Earth and is thus the basis for understanding the major interrelationships in a global perspective. In the first part, with a rich endowment of illustrations and photographic material, the well-introduced book deals with the essential processes and operations on the Earth's surface that lead to the formation of the vegetation cover with its distinctive zonation. In the second part, the individual vegetation zones as large-scale ecosystems (i.e. zonobiomes of the biosphere) are consistently described comparatively according to certain criteria. In a short and compact form, the main characteristics and structures as well as examples of ecosystem processes are discussed. The large-scale ecosystems are also the basis and reference system for all anthropogenic changes that have drastically altered vegetation over the last millennia, but especially in the 20th century. This book is a translation of the original German 1st edition Vegetation und Klima by Siegmar-W. Breckle and M. Daud Rafiqpoor, published by Springer-Verlag GmbH Germany, part of Springer Nature in 2019. The translation was done with the help of artificial intelligence (machine translation by the service DeepL.com). A subsequent human revision was done primarily in terms of content, so that the book will read stylistically differently from a conventional translation. Springer Nature works continuously to further the development of tools for the production of books and on the related technologies to support the authors. Authors Siegmar-W. Breckle long-time professor and head of the Department of Ecology at the University of Bielefeld (Germany). He continued the multi-volume work "Ecology of the Earth" by Heinrich Walter, published numerous articles and books on the ecology of many regions, especially the drylands combined with countless study trips around the globe. His research in deserts, tropics and high mountains is the basis for the corresponding chapters in this book. M. Daud Rafiqpoor, long-time research associate of the Academy of Sciences and Literature in Mainz and coordinator of two ecologically oriented long-term projects of this academy ("Three-dimensional Landscape Classification of the Tropics and Subtropics" and "Biodiversity in Change"). Numerous study trips in almost all tropical and subtropical mountains of the world. Publication of many papers and books on the geography and ecology of tropical and subtropical high mountains and Afghanistan.
I General Part -- Part A - Ecological Basics (Autoecology) -- Part B - Ecological Basics (Synecology) -- Part C - Ecological Systems and Ecosystem Biology -- II Special Part -- Part D - ZB I: Zonobiome of the evergreen tropical rainforest or equatorial humid diurnal climate -- Part E - ZB II: Zonobiome of savannas, deciduous forests and grasslands of the tropical summer rainfall region -- Part F - ZB III: Zonobiome of hot deserts or subtropical arid climate -- Part G - ZB IV: Zonobiome of hardwoods or Mediterranean winter rainfall regions -- Part H - ZB V: Zonobiome of laurel forests or warm temperate humid climate -- Part I - ZB VI: Zonobiome of winter barren deciduous forests or temperate nemoral climate -- Part J - ZB VII: Zonobiome of steppes and cold deserts or arid temperate climate -- Part K - ZB VIII: Zonobiome of hardwood forests or temperate arid climate. Part K - ZB VIII: Zonobiome of taiga or cold temperate boreal climate -- Part L - ZB IX: Zonobiome of tundra or arctic climate -- Part M - Summary, conclusions -- III Final part.
Keywords: Geography; Physical geography; Environment; Agriculture; Biotic communities; Biodiversity; Geography; Earth System Sciences; Environmental Sciences; Agriculture; Ecosystems; Biodiversity